2015
DOI: 10.1039/c5ta06813d
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine-conducted defect repairment and seed crystal-mediated vapor growth process for controllable preparation of efficient and stable perovskite solar cells

Abstract: A facile MaCl-assisted STCVD method is developed, and the novel defect repairment and seed crystal-mediated growth behavior is reported for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 58 publications
(101 reference statements)
0
41
1
Order By: Relevance
“…A few works have proved that the poor quality of PbI 2 films with large amounts of colloid suspensions and needle‐shaped solvation intermediates leads to porous perovskite films with incomplete conversion during solution process . Lately, we found that the introduction of Cl element in CVD process might effectively repair the inherent defect on PbI 2 template . However, to date the fundamental question still remains regarding the exact roles of Cl additive in gas‐phase growth process of MAPbI 3 (Cl).…”
Section: Discussionmentioning
confidence: 99%
“…A few works have proved that the poor quality of PbI 2 films with large amounts of colloid suspensions and needle‐shaped solvation intermediates leads to porous perovskite films with incomplete conversion during solution process . Lately, we found that the introduction of Cl element in CVD process might effectively repair the inherent defect on PbI 2 template . However, to date the fundamental question still remains regarding the exact roles of Cl additive in gas‐phase growth process of MAPbI 3 (Cl).…”
Section: Discussionmentioning
confidence: 99%
“…as a mixture with PbI 2 in DMF (and then MAI converted the film to MAPbI 3 perovskite). [50,51] To form this mixture, PbI 2 powder first reacted with HI, forming light yellow needle-like 1D HPbI 3 non-perovskite compound.…”
Section: Two-step Conversionmentioning
confidence: 99%
“…A small-scale PCE of g = 11.1% has been achieved with this technique. [185] As larger grain sizes tend to lead better performance, PCE of g = 13.8% for a small device area could be reached with enhanced photocurrent and open-circuit voltage. [183] Experiments with different metal halide base layers of PbI 2 , PbBr 2 , and SnI 2 to then convert with MAI were reported by Wang et al [184] The best outcome of the study was a g = 12.3% PCE small-scale MAPI device which showed no decline of performance even after 100 days of storage in humid air and 40% relative humidity.…”
Section: Perovskite Deposition Typementioning
confidence: 99%